2020
DOI: 10.3389/fvets.2020.522551
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory and Behavioral Responses of Buffaloes With and Without Direct Sun Exposure During Abnormal Environmental Condition in Marajó Island, Pará, Brazil

Abstract: This study aimed to assess the effect of thermal-hydraulic variables in female buffaloes with or without direct solar exposure in a year of strong El Niño through behavior responses and infrared thermography to reinforce the environmental comfort indicators, in Marajó Island, Pará, Brazil. The experiment was carried out in Cachoeira do Arari municipality and 20 female Murrah buffaloes were randomly assigned to two groups: Group WS (n = 10) was kept in pickets with native trees. Group NS (n = 10) was kept in cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
3
9
2
Order By: Relevance
“…Results showed only a low correlation (r 2 = 0.24) between orbital region and body temperature but produced a positive correlation between the orbital and anal regions (r 2 = 0.43). Their findings differ from those reported by Athaíde et al [61], who found a positive correlation (r 2 = 0.65) of the maximum, median, and minimum temperatures of the lacrimal caruncle of eye and orbital region with the rectal temperatures of female Murrah This study compared the thermal response of the lacrimal caruncle of the eye in four healthy bovines under conditions of pain produced by second-degree claudication of a pelvic limb [54]. The animals were subjected to a Sprecher test [57] to assess gait.…”
Section: Orbital Region (Regio Orbitalis)contrasting
confidence: 90%
See 2 more Smart Citations
“…Results showed only a low correlation (r 2 = 0.24) between orbital region and body temperature but produced a positive correlation between the orbital and anal regions (r 2 = 0.43). Their findings differ from those reported by Athaíde et al [61], who found a positive correlation (r 2 = 0.65) of the maximum, median, and minimum temperatures of the lacrimal caruncle of eye and orbital region with the rectal temperatures of female Murrah This study compared the thermal response of the lacrimal caruncle of the eye in four healthy bovines under conditions of pain produced by second-degree claudication of a pelvic limb [54]. The animals were subjected to a Sprecher test [57] to assess gait.…”
Section: Orbital Region (Regio Orbitalis)contrasting
confidence: 90%
“…Results showed only a low correlation (r 2 = 0.24) between orbital region and body temperature but produced a positive correlation between the orbital and anal regions (r 2 = 0.43). Their findings differ from those reported by Athaíde et al [ 61 ], who found a positive correlation (r 2 = 0.65) of the maximum, median, and minimum temperatures of the lacrimal caruncle of eye and orbital region with the rectal temperatures of female Murrah buffaloes under two climatic conditions: with and without access to shade. Another study that included buffaloes ( Bubalus bubalis ) reported that ocular temperatures in the orbital region had a positive correlation (r 2 = 0.92) with body temperatures in animals fed in open pasture [ 62 ].…”
Section: Orbital Region ( Regio Orbitalis )contrasting
confidence: 86%
See 1 more Smart Citation
“…Earlier studies have also reported a strong negative correlation between IHTI and RT in dairy cows in different seasons in the tropics [30]. On the other hand, studies have shown that BTCI was positively correlated with mean air temperature, which indicates thermal stress at higher temperatures [31]. Three physiological index models obtained in the present study were positively correlated with buffalo physiological indicators, especially with BST and RR.…”
Section: Discussionsupporting
confidence: 73%
“…Both groups had access to water and mineral salt ad libitum . The sample used in this study of 10 buffaloes per group was the same used in the Santos et al ( 26 ) and Athaide et al ( 27 ). In this study, only clinically healthy buffaloes were selected.…”
Section: Methodsmentioning
confidence: 99%